Cerebellar Morphology and Procedural Learning Impairment in Neuroleptic-Naive Youth at Ultrahigh Risk of Psychosis. (March 2014) - Dean, Derek J.; Bernard, Jessica A.; Orr, Joseph M.; Pelletier-Baldelli, Andrea; Gupta, Tina; Carol, Emily E.; Mittal, Vijay A.
Despite evidence suggesting a role for cerebellar abnormalities in the pathogenesis of psychosis, the structure has yet to receive attention in individuals at ultrahigh risk for psychosis (UHR). Accumulating research has suggested that the cerebellum helps modulate cognition and movement, domains in which UHR individuals show impairment; understanding putative markers of risk, such as structural abnormalities and behavioral correlates, is essential. In this study, participants underwent a high-resolution structural brain scan and participated in a pursuit rotor experiment. Cerebellar regions associated with movement (anterior cerebellum) and cognition (crus I) were subsequently analyzed. UHR participants showed impaired performance on the pursuit rotor task, learned at a slower rate, and showed smaller cerebellar volumes compared with control participants. Left crus I volume was significantly associated with poor rate of learning. The present results suggest that cerebellar abnormalities and their behavioral correlates (poor learning and motor control) precede the onset of psychosis.